Preparation and application of efficient self-supporting difunctional electrolytic alkaline seawater catalyst

By forming a nanosheet-shaped FeOOH-NiAl-LDH catalyst on the foam nickel framework and anchoring FeOOH active species on the catalyst surface, the problem of instability of traditional catalyst structure is solved, and stable cracking of alkaline seawater is achieved under high current density, significantly improving the activity and stability of the catalyst.

CN120006340AInactive Publication Date: 2025-05-16山西能源学院
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510267245.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2025-05-16
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The structure of traditional self-supported electrolytic alkaline seawater catalysts is unstable, difficult to operate for a long time under high current density, and cannot effectively resist corrosion and poisoning in seawater.

Method used

The FeOOH-NiAl-LDH catalyst with a nanosheet-like structure was formed on the foam nickel skeleton by hydrothermal growth method, and the FeOOH active species were anchored on the catalyst surface by a normal temperature impregnation and etching method to form a stable self-supporting structure.

Benefits of technology

The stable cracking of alkaline seawater by the catalyst under industrial current density conditions was achieved, with a lifespan of 1,000 hours, and the surface morphology was still in a nanosheet-like structure, which significantly improved the activity and stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120006340A_ABST
    Figure CN120006340A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electro-catalysis, and particularly discloses preparation and application of an efficient self-supporting bifunctional electrolytic alkaline seawater catalyst.The catalyst is of a self-supporting stable structure formed by loading FeOOH-NiAl-LDH of a nano-sheet structure on a foamed nickel framework, and the preparation method comprises the following steps that 1, a hydrothermal growth method is adopted, foamed nickel serves as a substrate, and the self-supporting stable structure is formed; the preparation method comprises the following steps: weighing nickel nitrate hexahydrate, aluminum nitrate nonahydrate and urea, dispersing in deionized water, uniformly stirring, transferring into a reaction kettle, keeping at 100-120 DEG C for 10-12 hours, naturally cooling, washing and drying; and (2) adopting a room-temperature dipping etching method, taking flaky sodium hydroxide, dissolving the flaky sodium hydroxide in deionized water, fully dissolving, adding potassium ferrate to form a purple-red FeOOH colloid, putting the NiAl-LDH electrode prepared in the step (1) into the colloid, and dipping and etching at the room temperature of 25 DEG C for 12-24 hours to obtain the FeOOH-NiAl-LDH electrode. The scheme is mainly used for preparing the electrolytic seawater catalyst, and the problem that a traditional self-supporting electrolytic alkaline seawater catalyst is unstable in structure is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrocatalysis, and in particular relates to the preparation and application of a highly efficient self-supporting bifunctional electrolytic alkaline seawater catalyst. Background Art

[0002] Hydrogen energy is a clean and efficient secondary energy source. Against the backdrop of the increasing scarcity of freshwater resources worldwide, the production of "green hydrogen" through electrocatalytic cracking of seawater, which accounts for 96.5% of water resources, is a promising technology that is conducive to the sustainable development of energy and the environment.

[0003] Similar to freshwater splitting, seawater electrolysis mainly consists of two half reactions, including the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. OER, the key half-reaction in water electrolysis, has a higher energy barrier and slower kinetics, resulting in high energy consumption, which makes this process overly dependent on precious metal-based catalysts. Although significant progress has been made in the development of efficient non-precious metal materials as alternatives to precious metal catalysts, most materials cannot meet the requirements of long-term operation at high current densities in practical applications, which poses greater challenges to the design and manufacture of electrocatalysts. In addition, the complex composition of seawater also poses major challenges to the efficient and continuous electrolysis of seawater due to the corrosion of aggressive chloride ions and the presence of microorganisms, bacteria and insoluble precipitates (Ca(OH) 2 Mg(OH) 2 The activity and service life of the electrode are greatly affected by the poisoning of active sites by salts, etc. Therefore, it is urgent to develop catalysts with high activity and resistance to seawater corrosion.

[0004] In previous studies, various highly efficient non-precious metal catalysts have made some progress as alternatives to precious metal catalysts. In particular, nickel-based catalysts, which have good electrolytic water splitting activity and are cheap and readily available, are widely considered to be effective materials for seawater splitting. At present, the modified nickel-based catalysts designed for electrocatalytic alkaline seawater oxidation mainly focus on the introduction of non-metallic elements such as nitrogen, sulfur, phosphorus, and boron by hydrothermal or vapor deposition methods, and the oxygen-containing anions formed in situ or during the anodic oxidation process resist Cl - However, this high-temperature preparation process will cause irreversible damage to the nickel foam skeleton. The process of catalyst surface reconstruction to form metal hydroxide oxides and the violent impact of large-sized bubbles on the catalytic phase surface will affect the stability of the catalyst. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation and application of a highly efficient self-supporting bifunctional electrolysis alkaline seawater catalyst, which solves the problem of structural instability of traditional self-supporting electrolysis alkaline seawater catalysts.

[0006] In order to achieve the above object, the technical scheme of the present invention is as follows: a preparation of a highly efficient self-supporting bifunctional catalyst for electrolysis of alkaline seawater: the catalyst is a nano-sheet structure of FeOOH-NiAl-LDH loaded on a foam nickel skeleton to form a self-supporting stable structure, and its preparation comprises the following steps:

[0007] (1) Using a hydrothermal growth method, with nickel foam as the substrate, 0.5-2 mmol nickel nitrate hexahydrate, 0.5-1 mmol aluminum nitrate nonahydrate, and 2-4 mmol urea were weighed and dispersed in 20-40 mL deionized water, stirred evenly, and then transferred to a reactor, sealed in a shell, and then transferred to a homogeneous reactor and kept at 100-120° C. for 10-12 hours. After natural cooling, the product was repeatedly rinsed with deionized water and alcohol, and dried in a vacuum oven to obtain a NiAl-LDH electrode;

[0008] (2) Using a room temperature immersion etching method, flake sodium hydroxide is dissolved in deionized water and fully dissolved, and then potassium ferrate is added thereto and stirred evenly to form a purple-red FeOOH colloid. The NiAl-LDH electrode prepared in step (1) is placed in the above colloid and immersed and etched at room temperature of 25°C for 12 to 24 hours to obtain a FeOOH-NiAl-LDH electrode.

[0009] Furthermore, in step (1), the amount of nickel nitrate hexahydrate used is 2 mmol, the amount of aluminum nitrate nonahydrate used is 1 mmol, the amount of urea used is 4 mmol, and the amount of deionized water used is 20 ml.

[0010] Furthermore, in step (2), the high concentration alkaline solution etches Al in NiAl-LDH while anchoring other metals on the catalyst surface.

[0011] Furthermore, the strong alkaline environment and the strong oxidizing property of potassium ferrate in step (2) have a passivating effect on Al species.

[0012] Furthermore, in step (2), the concentration of sodium hydroxide is 4-8 mol / L, the amount of potassium ferrate is 10-50 mg, and the amount of deionized water is 20-40 mL.

[0013] Furthermore, the nanosheet-structured FeOOH-NiAl-LDH self-supporting catalyst has a nanosheet thickness of 10 to 30 nm.

[0014] Furthermore, the FeOOH-NiAl-LDH self-supporting structure catalyst with a nano-sheet structure can be used for oxygen evolution at the anode and hydrogen evolution at the cathode of an electrolytic cell.

[0015] Furthermore, the FeOOH-NiAl-LDH self-supporting structure catalyst with a nanosheet structure can be used to stably crack alkaline seawater to produce hydrogen for 1000 hours under industrial current density conditions.

[0016] The technical solution of the present invention achieves the following beneficial technical effects:

[0017] 1. The present invention provides a method for preparing a highly efficient self-supporting bifunctional catalyst for electrolysis of alkaline seawater. Nanosheet NiAl-LDH is uniformly grown on a commercial nickel foam substrate using a traditional hydrothermal method. The nanosheet structure provides the catalyst precursor with abundant active sites and facilitates the etching of Al species by the NaOH solution in the second step.

[0018] 2. The present invention uses NiAl-LDH as a precursor, and while etching the Al part by room temperature immersion etching, the FeOOH active species are anchored on the electrode surface, and the surface reconstruction of the catalyst during the OER process is avoided. The catalyst exhibits excellent electrocatalytic activity and stability when used to crack alkaline natural seawater under industrial current density conditions.

[0019] 3. During the room temperature immersion etching process, the strong alkaline environment and the strong oxidizing property of potassium ferrate passivate the Al species, making the catalyst effectively resistant to Cl in natural seawater. - It is resistant to corrosion by other substances and shows excellent stability when used in alkaline natural seawater cracking.

[0020] 4. Compared with traditional transition metal self-supporting oxygen evolution catalysts, this catalyst does not use non-metallic elements such as nitrogen, sulfur, phosphorus, and boron to modify the catalyst, avoiding the reconstruction of the catalyst during the catalytic oxygen evolution reaction, which leads to its structural instability. -2 The physical strength of the catalyst did not decay after 1000h of oxygen evolution test under industrial current density conditions. Scanning electron microscopy showed that the catalyst surface still had a nanosheet structure after the stability test.

[0021] 5. The present invention abandons the traditional non-metallic doping idea. First, metal Al and Ni salts are used to prepare NiAl-LDH precursors on a commercial nickel foam substrate. Next, the idea that the preparation environment of the catalyst should be as close as possible to the use environment is creatively proposed. A strong alkaline solution rich in FeOOH colloid is used to immerse and etch the NiAl layered double hydroxide at room temperature. The passivated aluminum generated in this process effectively resists Cl in seawater. - At the same time, the FeOOH anchored on the catalyst surface acts as an active species and effectively prevents the catalyst from being reconstructed during the anodic oxidation process, which greatly improves the activity and stability of the catalyst in the high current cracking of alkaline natural seawater.

[0022] 6. This method has simple steps, low raw material cost, controllable process, and the prepared catalyst has a high -2The physical strength of the electrode was not attenuated after 1000 hours of OER test in alkaline natural seawater splitting under industrial current density conditions, and the surface morphology was still a nanosheet structure. This finished electrode meets the objective demand of industrial seawater splitting equipment for long-term and high-efficiency catalytic materials, and is expected to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The SEM image of the product obtained in Example 1 of the present invention is shown;

[0024] Figure 2 The XRD diagram of the product obtained in Example 1 of the present invention is shown;

[0025] Figure 3 represents the Al 2p XPS graph of the product obtained in Example 1 of the present invention;

[0026] Figure 4 The OER and HER polarization curves of the products obtained in Example 1 of the present invention and Comparative Example 1 in an alkaline electrolyte are shown;

[0027] Figure 5 The Vt polarization curve of the product obtained in Example 1 of the present invention undergoing OER in alkaline natural seawater;

[0028] Figure 6 The SEM image of the product obtained in Example 1 of the present invention after the OER test was carried out in alkaline natural seawater for 1000 hours. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods, but the protection scope of the present invention is not limited to the following embodiments.

[0030] Embodiment 1:

[0031] (1) Using the hydrothermal growth method, with clean nickel foam (0.5 mm) as the substrate, 2 mmol nickel nitrate hexahydrate, 1 mmol aluminum nitrate nonahydrate, and 4 mmol urea were weighed and dispersed in 20 mL deionized water, stirred evenly and transferred to a reactor, sealed in a shell, and then transferred to a homogeneous reactor at 120°C for 12 h. After cooling naturally, the product was repeatedly rinsed with deionized water and alcohol, and dried in a vacuum oven to obtain a NiAl-LDH electrode;

[0032] (2) Using the room temperature immersion etching method, 4.8 g of sodium hydroxide flakes were dissolved in 20 mL of ionized water, and then 10 mg of potassium ferrate was added thereto and stirred evenly to form a purple-red colloid. The NiAl-LDH electrode prepared in step (1) was placed in the above colloid, and after immersion etching at room temperature for 12 h, a FeOOH-NiAl-LDH electrode was obtained.

[0033] Embodiment 2:

[0034] (1) Using the hydrothermal growth method, with clean nickel foam (0.5 mm) as the substrate, 2 mmol nickel nitrate hexahydrate, 1 mmol aluminum nitrate nonahydrate, and 6 mmol urea were weighed and dispersed in 20 mL deionized water, stirred evenly and transferred to a reactor, sealed in a shell, and then transferred to a homogeneous reactor at 120°C for 12 h. After cooling naturally, the product was repeatedly rinsed with deionized water and alcohol, and dried in a vacuum oven to obtain a NiAl-LDH electrode;

[0035] (2) Using the room temperature immersion etching method, 4.8 g of sodium hydroxide flakes were dissolved in 20 mL of ionized water, and then 10 mg of potassium ferrate was added thereto and stirred evenly to form a purple-red colloid. The NiAl-LDH electrode prepared in step (1) was placed in the above colloid, and after immersion etching at room temperature for 12 h, a FeOOH-NiAl-LDH electrode was obtained.

[0036] Embodiment 3:

[0037] (1) Using the hydrothermal growth method, with clean nickel foam (0.5 mm) as the substrate, 2 mmol nickel nitrate hexahydrate, 1 mmol aluminum nitrate nonahydrate, and 4 mmol urea were weighed and dispersed in 20 mL deionized water, stirred evenly and transferred to a reactor, sealed in a shell, and then transferred to a homogeneous reactor at 120°C for 12 h. After cooling naturally, the product was repeatedly rinsed with deionized water and alcohol, and dried in a vacuum oven to obtain a NiAl-LDH electrode;

[0038] (2) Using the room temperature immersion etching method, 4.8 g of sodium hydroxide flakes were dissolved in 20 mL of ionized water, and then 30 mg of potassium ferrate was added thereto and stirred evenly to form a purple-red colloid. The NiAl-LDH electrode prepared in step (1) was placed in the above colloid, and after immersion etching at room temperature for 12 h, a FeOOH-NiAl-LDH electrode was obtained.

[0039] Comparative Example 1:

[0040] The difference between Comparative Example 1 and Example 1 is that step (2) is omitted, and the rest is the same as Example 1 to obtain a NiAl-LDH electrode.

[0041] The electrodes obtained in Example 1 and Comparative Example 1 were subjected to water electrolysis OER and HER tests in 1M KOH electrolyte. The electrochemical tests were carried out on an electrochemical workstation (CHI760E) using a standard three-electrode system, in which the Hg / HgO electrode was the reference electrode, the graphite electrode was the counter electrode, and the products prepared in Example 1 and Comparative Example 1 of the present invention were the working electrodes (geometric area 1 cm×1 cm).

[0042] Linear sweep voltammetry (LSV) in O 2 In saturated electrolyte, 5 mV s -1 The scan rate is measured, formula E vs.RHE =E vs.Hg / HgO +0.059×pH+0.098 calculated potential and reversible hydrogen electrode (RHE) potential. In 1M KOH natural seawater electrolyte solution, the electrode prepared in Example 1 was tested by chronopotentiometry at 1A cm -2 Stability of oxygen evolution in seawater under current density.

[0043] The FeOOH-NiAl-LDH catalyst prepared in Example 1 was tested using a scanning electron microscope (SEM). Figure 1 The SEM image of the FeOOH-NiAl-LDH catalyst obtained in Example 1 is given. It can be seen from the image that the catalyst prepared in Example 1 of the present invention is a nanosheet structure with a thickness of 10-30 nm.

[0044] The structure of the FeOOH-NiAl-LDH catalyst prepared in Example 1 was characterized by X-ray diffractometer (XRD). Figure 2 The XRD spectrum of the FeOOH-NiAl-LDH catalyst obtained in Example 1 is given; after comparison, the spectrum is consistent with the peak shape of the NiAl-LDH standard card (JCPDS22-0452), and the surface FeOOH species is amorphous or has a low degree of crystallinity.

[0045] The structure and valence state of the FeOOH-NiAl-LDH catalyst prepared in Example 1 were detected by X-ray photoelectron spectroscopy (XPS). Figure 3 The XPS spectrum of the FeOOH-NiAl-LDH catalyst obtained in Example 1 is given; after comparison, the FeOOH-NiAl-LDH catalyst prepared in Example 1 contains rich Al element.

[0046] Figure 4 The OER and HER polarization curves of the catalysts obtained in Example 1 and Comparative Example 1 in alkaline electrolyte are given. By comparison, the FeOOH-NiAl-LDH catalyst obtained in Example 1 has a high OER and HER polarization curves in alkaline electrolyte at 100 mA. -2 When the current is low, it exhibits an oxygen evolution (OER) and hydrogen evolution (HER) overpotential that is 50 to 100 mV lower than that of similar catalysts, reflecting its excellent catalytic activity for oxygen and hydrogen evolution.

[0047] Figure 5 The Vt polarization curve of the FeOOH-NiAl-LDH catalyst obtained in Example 1 for OER in alkaline natural seawater is given. -2After 1000h of OER test in alkaline natural seawater under current density, the voltage did not increase significantly, which reflects its good stability when applied to the electrolysis of alkaline seawater under industrial current density conditions.

[0048] Figure 6 The FeOOH-NiAl-LDH catalyst obtained in Example 1 is given at 1Acm -2 The SEM image of the OER test in alkaline natural seawater at a current density of 1000h shows that its structure still remains in the form of nanosheets, reflecting an extremely stable structure.

[0049] In summary, the present invention provides a highly active water electrolysis catalyst, which has a simple preparation process, is cheap and easy to obtain, exhibits good stability when applied to electrocatalytic cracking of alkaline seawater, and shows good industrial application prospects.

[0050] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a highly efficient self-supporting bifunctional electrolytic alkaline seawater catalyst, characterized in that: The catalyst is a nano-sheet structure of FeOOH-NiAl-LDH loaded on a nickel foam skeleton to form a self-supporting stable structure, and its preparation includes the following steps: (1) Using a hydrothermal growth method, with nickel foam as the substrate, 0.5-2 mmol nickel nitrate hexahydrate, 0.5-1 mmol aluminum nitrate nonahydrate, and 2-4 mmol urea were weighed and dispersed in 20-40 mL deionized water, stirred evenly, and then transferred to a reactor, sealed in a shell, and then transferred to a homogeneous reactor and kept at 100-120° C. for 10-12 hours. After natural cooling, the product was repeatedly rinsed with deionized water and alcohol, and dried in a vacuum oven to obtain a NiAl-LDH electrode; (2) Using a room temperature immersion etching method, flake sodium hydroxide is dissolved in deionized water and fully dissolved, and then potassium ferrate is added thereto and stirred evenly to form a purple-red FeOOH colloid. The NiAl-LDH electrode prepared in step (1) is placed in the above colloid and immersed and etched at room temperature of 25°C for 12 to 24 hours to obtain a FeOOH-NiAl-LDH electrode.

2. The method for preparing a highly efficient self-supporting bifunctional electrolytic alkaline seawater catalyst according to claim 1, characterized in that: In step (1), the amount of nickel nitrate hexahydrate used is 2 mmol, the amount of aluminum nitrate nonahydrate used is 1 mmol, the amount of urea used is 4 mmol, and the amount of deionized water used is 20 ml.

3. The method for preparing a highly efficient self-supporting bifunctional electrolytic alkaline seawater catalyst according to claim 1, characterized in that: In step (2), the strong alkaline environment etches Al in NiAl-LDH while anchoring other metals on the catalyst surface.

4. The method for preparing a highly efficient self-supporting bifunctional electrolytic alkaline seawater catalyst according to claim 1, characterized in that: In step (2), the strong alkaline environment and the strong oxidizing property of potassium ferrate passivate the Al species.

5. The method for preparing a highly efficient self-supporting bifunctional electrolytic alkaline seawater catalyst according to claim 1, characterized in that: In step (2), the concentration of sodium hydroxide is 4-8 mol / L, the amount of potassium ferrate is 10-50 mg, and the amount of deionized water is 20-40 mL.

6. The FeOOH-NiAl-LDH self-supporting structure catalyst with a nanosheet structure according to claim 1, characterized in that: The thickness of the nanosheets is 10 to 30 nm.

7. The FeOOH-NiAl-LDH self-supporting structure catalyst with a nanosheet structure according to claim 1, characterized in that: The catalyst can be used for oxygen evolution at the anode and hydrogen evolution at the cathode of the electrolyzer.

8. The FeOOH-NiAl-LDH self-supporting structure catalyst with a nanosheet structure according to claim 1, characterized in that: The catalyst can be used to stably crack alkaline seawater to produce hydrogen for 1000 hours under industrial current density conditions.

Citation Information

Cited By

  • Difunctional electrolyzed water / seawater hydrogen production catalyst, preparation method and application

    CN120866873A